Analyses of instruction for breath control while swimming the breaststroke - Hara, H.; Yoshioka, A.; Matsumoto, N.; Nose, Y.; Watanabe, R.; Shibata, Y.; Onodera, S. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of this research was to clarify the important factors preventing swimming apnea. We conducted the experiment with seven subjects using four pressure transducers simultaneously. These were connected to the control unit and the data were analyzed to detect pressure changes with the face in three different positions. We verified that trained swimmers vary the amount of air blown out of the nose and mouth independently. There was an interval between exhaling from the nose to exhaling from the mouth. In the case of instruction for beginners, in order to prevent swimming apnea it is effective if the instructor has the learner pronounce "Mnn" with the nose, then once that is completed, pronounce "Pha" or "Pa" from the mouth to blow out.